WORK EFFICIENCY OF INTEGRATED SERVICE POST CADRES IN MONITORING THE GROWTH AND DEVELOPMENT OF CHILDREN UNDER FIVE THROUGH THE USE OF THE E-POSYANDU KESEHATAN (EPOK) APPLICATION - Melly Damayanti; Nurul Aini Suria Saputri; Darwitri, Darwitri (International Journal of Social Science, 2025)
Integrated service post (Posyandu) cadres play a vital role in monitoring the growth and development of children under five, yet they often face challenges in work efficiency due to manual data recording and limited access to information. This study aimed to analyze the effect of the e-Posyandu Kesehatan (ePoK) application on the work efficiency of cadres in conducting child growth monitoring and stimulation. A quasi-experimental design with a one-group posttest-only approach was employed. A total of 60 cadres were selected using proportional stratified random sampling. Data were collected using a validated and reliable questionnaire consisting of seven dimensions: time efficiency, data accuracy, productivity, information access, digital competence, communication and coordination. The results of multiple linear regression showed that all dimensions simultaneously had a significant influence on work efficiency (F = 221.075; p < 0.05) with an Adjusted R² of 0.962. Partially, information access (β = 0.677) and productivity (β = 0.388) were the most dominant dimensions. It is concluded that ePoK enhances cadre efficiency by accelerating data access, increasing productivity, and simplifying workflows. It is recommended to strengthen digital training for cadres and expand the implementation of ePoK to other regions as part of a broader community-based health service improvement strategy